2021
DOI: 10.2298/tsci191201024l
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of PVDF/PES nanofibers with unsmooth fractal surfaces by electrospinning: A general strategy and formation mechanism

Abstract: Smaller fibers are welcome in many applications due to larger surface area, but there is a threshold for smallest fibers for a fixed spinning system. In order to further improve surface area, hierarchical structure is considered in this paper using electrospinning. A bi-solvent system is used in our experiment for fast solvent evaporation. Unsmooth nanofibers are obtained, and the formation mechanism is elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…And no significant phase separation was found from the figure, indicating that BTB was uniformly dispersed in the polymer carrier. The colour indicator film was made up of a large number of fibres with a large specific surface area, which helped to increase the responsiveness of the colour indicator film to external changes 17 . On the other hand, the small diameter of the fibres increased the specific surface area of the colour indicator film and improved sensitivity, so BTB‐6‐PLLA‐3‐PVP provided a favourable condition for later indication.…”
Section: Resultsmentioning
confidence: 99%
“…And no significant phase separation was found from the figure, indicating that BTB was uniformly dispersed in the polymer carrier. The colour indicator film was made up of a large number of fibres with a large specific surface area, which helped to increase the responsiveness of the colour indicator film to external changes 17 . On the other hand, the small diameter of the fibres increased the specific surface area of the colour indicator film and improved sensitivity, so BTB‐6‐PLLA‐3‐PVP provided a favourable condition for later indication.…”
Section: Resultsmentioning
confidence: 99%
“…The general approaches to fabricating smooth nanofibers are electrospinning ( Gao et al, 2021 ; Liu et al, 2021 ) and bubble electrospinning ( He and Qian, 2022 ; Qian and He, 2022 ). However, Lin, et al, 2021 suggested a general strategy for the fabrication of unsmooth nanofibers. Yao and He (2020 ) used the geometric potential theory to control the surface morphology of nanofibers.…”
Section: Resultsmentioning
confidence: 99%
“…When considering different approaches to describing the formation and dissipation of fogs one should mention physico-mathematical models involving the description of turbulent processes. The latter ones are the subject of research in different areas, for example, in modeling solvent evaporation in a moving jet of the spinning process [22,23]. In the problems of describing fog formation above rivers this approach allows modeling wave-like fog patterns along the river accompanied by dissipated whirling columns of fog similar to «steam devils» [24].…”
Section: Influence Of the Relief And Formation Of Turbulent Structuresmentioning
confidence: 99%